Role of Protective Fixed Bandages in the Prevention of Infection at the Standing Site of Catheters and Reliability of Their Fixation - N. A. Karpun; V. V. Moroz; A. M. Ovechkin; G. M. Klimova; V. G. Pasko; Yu. G. Tikhonov (Общая реаниматология, 2006)
The paper deals with the study of protective and fixed means in the prevention of bacterial contamination at the standing site of catheters used for different purposes and the reliability of their fixation. The study covered 136 patients and victims. Special means for fixing and protecting central venous and epidural catheters were applied in the study group. Adhesive plaster and gauze were used to protect and fix the standing site of catheters in the control group. High-technology protective fixed means have evident advantages, such as effective protection from bacterial contamination, reliable fixation of catheters used for different purposes, comfort for patients, safety, and serviceability in the work of medical staff. The routine use of fixation as an adhesive plaster and gauze fails to provide a valid protection and a reliable  fixation  in  critically  ill  patients.